Cooling enhancement in an air-cooled finned heat exchanger by thin water film evaporation - Song, CH; Lee, DY; Ro, ST (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
A theoretical analysis on the cooling enhancement by applying evaporative cooling to an air-cooled finned heat exchanger is presented in this work. A two-dimensional model on the heat and mass transfer in a finned channel is developed adopting a porous medium approach. Based on this model, the characteristics of the heat and mass transfer are investigated in a plate-fin heat exchanger with the interstitial surface fully covered by thin water film. Assuming that the Lewis number is unity and the water vapor saturation curve is linear, exact solutions to the energy and vapor concentration equations are obtained. The cooling effect with application of evaporative cooling was found to be improved considerably compared with that in the sensible cooler. This is because the thermal conductance between the fin and the air increases due to the latent heat transfer caused by the water evaporation from the fin surface. It is also found that the cooling enhancement depends greatly on the fin thickness. If the fin is not sufficiently thick, the cooling enhancement by the evaporative cooling decreases since the fin efficiency drops considerably due to the water evaporation from the fin surface. The fin thickness in the evaporative cooler should be increased larger than that in the sensible cooler to take full advantage of the cooling enhancement by the water evaporation. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: MASS-TRANSFER; POROUS-MEDIA; CONVECTION; CHANNEL